2016
DOI: 10.4103/0974-7796.184901
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial comparing intracorpus spongiosum block versus intraurethral lignocaine in visual internal urethrotomy for short segment anterior urethral strictures

Abstract: Objectives:The primary objective was to compare the effectiveness in pain relief of intracorpus spongiosum block (ICSB) versus intraurethral topical anesthesia (TA) using 2% lignocaine jelly for performing visual internal urethrotomy (VIU) for short segment anterior urethral strictures.Materials and Methods:It was a randomized, parallel group controlled trial. Participants are adult patients with a single anterior urethral stricture up to 2 cm in length. Patients were allocated to two intervention groups with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Except for the transperineal block, all other methods usually require supplementary sedation [10]. The randomized controlled trial conducted by Biswal et al concluded that intraurethral lignocaine had a higher failure rate as compared to the spongiosal block [11]. Our technique described herein achieves acceptable analgesia without the need for any sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the transperineal block, all other methods usually require supplementary sedation [10]. The randomized controlled trial conducted by Biswal et al concluded that intraurethral lignocaine had a higher failure rate as compared to the spongiosal block [11]. Our technique described herein achieves acceptable analgesia without the need for any sedation.…”
Section: Discussionmentioning
confidence: 99%